Kepuasan Sebagai Pemoderasi Pengaruh Keadilan Distributif, Penegakan Sanksi pada Kepatuhan Wajib Pajak Hotel dan Restoran - Budhiarsana, Wayan; Dwirandra, A.A.N.B.; Wijana Asmara Putra, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
Distributive justice and  the enforcement of sanctions have not a linear effect on hotels and restaurants tax compliance because contingencies effect from taxpayer satisfaction. The study intends to determine  distributive justice, enforcement of sanctions and the satisfaction of taxpayer effects  on hotels and restaurants tax compliance. The study take 76 respondents hotel and restaurant in Tabanan Regency,  by the Slovin formula and determined randomly. Collecting data using questionnaires from some previous researchers. Data analysis using multiple regression analysis and Moderated Regression Analysis. Positive effect showed by distributive justice, sanctions enforcement, and taxpayer satisfaction  on hotels and restaurants tax compliance. The taxpayer satisfaction moderate the effect of the enforcement of sanctions on hotels and restaurants taxpayer compliance, but it doesn’t moderate the distributive justice effect on hotels and restaurants taxpayer compliance.
Keywords: Compliance, Justice, Sanctions Enforcement, Satisfaction.